2011
DOI: 10.1007/s00056-011-0033-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of orthognathic surgery on periodontal tissues

Abstract: Orthognathic surgery has a statistically significant effect on the development of gingival recessions. However, this effect may not necessarily clinically impair the esthetic appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It can be speculated that that the periodontal status of the teeth in the symphyseal region would have been unchanged even if the described procedure had not been applied. We are of the opinion that it is unlikely and that our treatment concept has prevented gingival recession particularly when the data from the literature are taken into consideration.…”
Section: Discussionmentioning
confidence: 96%
“…It can be speculated that that the periodontal status of the teeth in the symphyseal region would have been unchanged even if the described procedure had not been applied. We are of the opinion that it is unlikely and that our treatment concept has prevented gingival recession particularly when the data from the literature are taken into consideration.…”
Section: Discussionmentioning
confidence: 96%
“…5 Le Fort I and sagittal osteotomies are used to correct most skeletal problems in orthognathic surgery. 22 These procedures are quite invasive and can cause a number of postoperative complications, including vertical loss of alveolar bone. Le Fort I osteotomy can have an impact on the vascular supply of the upper teeth.…”
Section: Discussionmentioning
confidence: 99%
“…23 This injury to the medullary nutritional system may cause transient ischemia and insipid osteonecrosis, which may be related to dehiscence formation. Gingival recession was reported 22 in 0.8% of patients after Le Fort I, due to a postoperative complication involving partial necrosis of the maxillary segment. In addition, alveolar bone loss may also be related to damage caused by overheating of the alveolar bone with the use of reciprocating saws, drills, and chisels.…”
Section: Discussionmentioning
confidence: 99%
“…During orthognathic surgeries, there is convincing evidence that suggests, there is significant incidence of periodontal injury in the region of segmental osteotomy (14) . It has been reported that orthognathic surgeries have a marked effect in the development of gingival recessions (15) .…”
Section: Periodontics-oral Surgerymentioning
confidence: 99%